Relationship between blood pressure and blood flow in newborn preterm infants. Issue 1 (2nd May 2007) - Groves, A M; Kuschel, C A; Knight, D B; Skinner, J R
Abstract : Background: Arterial blood pressure remains the most frequently monitored indicator of neonatal circulatory status. However, studies of systemic perfusion in neonates have often shown only weakly positive associations with blood pressure. Objectives: To examine the relationship between invasively monitored arterial blood pressure and four measurements of systemic perfusion: left and right ventricular outputs, superior vena caval (SVC) flow and descending aortic (DAo) flow. Design: Echocardiographic assessments of perfusion were performed four times in the first 48 h of postnatal life in a cohort of 34 preterm (<30 weeks) infants. Arterial blood pressure was monitored invasively over the exact duration of the echocardiogram. Results: In the first 48 h of postnatal life there was no evidence of a positive association between blood pressure and volume of blood flow in any of the four vessels studied. At 5 h postnatal age there was a weak but significant inverse correlation between volume of SVC flow and arterial blood pressure (p = 0.04). A similar but non-significant trend was seen at 12 h postnatal age. Conclusions: Infants with reduced systemic perfusion tend to have normal or high blood pressure in the first hours of life, suggesting that a high systemic vascular resistance may lead to reduced blood flow. Low blood pressure does not correlate with poor perfusion in the first 48 h of postnatal life in sick preterm infants.